The Effectiveness of Using Differentiated Instruction on Science Learning Achievement for Grade 5 Bhutanese Students - Selden, Chimi; Sakulwongs, Nipaporn (Journal of Research and Curriculum Development, 2024)
The purposes of the study were to examine the effectiveness of using Differentiated Instruction (DI) on Science learning achievement and learning satisfaction of grade 5 Bhutanese Students. This mixed- method research adopted a cluster random sampling method to select a sample group consisting of 30 students from one of the primary schools in Bhutan. The instruments used for the study were lesson plans, learning achievement tests and a semi-structured interview. The validity of the research instruments were validated by 3 experts with the result of the IOC index ranges from -1 to +1. The study used pre-test and post-test method to collect quantitative data and semi-structured interview to collect qualitative data. The pre-test and post-test were conducted before and after the treatment to find out the level of students’ learning achievement. The semi-structured interview was administered after the post-test to find out the students’ learning satisfaction in Science. The result of learning achievement was analyzed using a paired sample t-test. It was found that the post-test mean score (14.37) was higher than the pre-test mean score (8.58) with the mean difference of 5.79. Further, the significance (p) value was .01 which indicated using differentiated instruction on Science learning was effective. Additionally, the findings from semi-structured interview concluded that participants expressed high levels of learning satisfaction. Therefore, DI approach should be applied and implemented in schools as it creates new and diverse learning environments to accommodate students’ diverse learning requirements, irrespective of their academic status or standing in society.